3D interactive internet application based on VRML - Gao, Bo (2008)
This dissertation focuses on three aspects. The first one is analyzing the reason why VRML became the international standard for creating interactive virtual environment over the Internet. An investigation on the basic structure and fundamental mechanism of VRML is made. Second aspect is on finding out all advantages and disadvantages of VRML by comparing it with other 3D authoring languages and formats. Last and the most important aspect is on proposing a set of non-proprietary mechanisms and the ways of implementation for creating a shared multi-user VRML environment.